Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

Seeding of Au on CdSe/CdS nanoplates using Langmuir-Blodgett technique - Das, Subhasis; Satpati, Biswarup; Chauhan, Himani; Deka, Sasanka; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (RSC Advances, 2016)
Oleyl amine capped CdSe/CdS nanoplates were synthesized by hot injection technique which formed a stable monolayer over both a water subphase and an aqueous HAuCl4 subphase using a Langmuir-Blodgett trough. Au islands were generated at the edge as well as on one specific surface of the flat nanoplates by exploiting the reducing capacity of oleyl amine to form Au nanoseeds from AuCl4- ions. The initial Au nanoseeds changed to a shell surrounding these nanoplates on prolonged exposure to the subphase containing the Au precursor. Monolayer of the hybrid structures was deposited onto suitable substrates for characterization by a number of different techniques and to study the photocatalytic activity. The same substrate with the monolayers could be re-used in several cycles of photocatalysis.